East of Europe, West of Asia: Historical Development of Hungarian Public Finances from the Age of Dualism to the Present - Milanov, Viktor (Public Finance Quarterly, 2020)
Csaba LentnerL’Harmattan Publishing House, Paris – Budapest, 2020